Use of an Elastomeric Knee Brace in Patellofemoral Pain Syndrome: Short-Term Results - Uboldi, Francesco Mattia; Ferrua, Paolo; Tradati, Daniele; Zedde, Pietro; Richards, Jim; Manunta, Andrea; Berruto, Massimo (Joints, 2018)
Purpose This article verifies the effectiveness of a new brace on patellofemoral pain syndrome (PFPS) in adjunct to a specifically developed rehabilitation program.Methods Two groups of 30 patients with PFPS were prospectively and randomly allocated to a rehabilitation protocol, with (group A) or without (group B) the use of a specific brace. All the patients were assessed at 3, 6, and 12 months using the disease-specific Kujala scale and a visual analog scale (VAS) for pain; time to return to sport and patient satisfaction with the brace were also recorded.Results Kujala scale's values showed constant and progressive improvement. The mean score at 6 months was 79.8 ± 6.8 points in group A and 76.8 ± 8.6 in group B, rising at 12 months to 80.9 ± 7.5 in group A and 78.4 ± 8.3 in group B. VAS scores significantly differed (p < 0.05) between the two groups at both 6 and 12 months; the score recorded at 12 months was 0.9 ± 1.3 in the brace-treated group and 1.8 ± 1.6 in the controls. The patients who used a brace showed a quicker return to sports and 75% of the patients in this group were satisfied.Conclusion All the scores improved progressively in both groups. The most significant improvement concerned pain, showing that the brace used in this study may allow a better subjective outcome and a quicker return to sport.Level of Evidence Level II, prospective randomized controlled trial.
Keywords: knee joint; patellofemoral pain syndrome; braces; athletes